PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MENGGUNAKAN FITUR TIKTOK SHOP DALAM APLIKASI TIKTOK PADA MAHASISWA/I INSTITUT STIAMI - Trie Andari Ratna Widyastuti; Mamas Sugiarti (JAMBIS : Jurnal Administrasi Bisnis, 2023)
With the Tiktok Shop feature, it has an impact on various types of people, especially the millennial generation. This millennial generation generally likes to use technology to facilitate activities, including shopping activities. This millennial generation has had a significant impact on the Tiktok Shop feature in the Tiktok application. This study aims to examine the impact of perceived ease of useand service quality on consumer decisions to utilize the TikTok Shopfeature within the TikTok application. The research employs a quantitative methodology, utilizing research instruments in the form of questionnaries and existing literature. The target population for this study consists of users of the TikTok Shop feature among the 2019 Class of STIAMI Institute Students. The sampling technique employeed is probability sampling, specifically the population sampling method, with a total sample size of 150 individuals. The data collected is analyzed using multiple linearregression analysis with the assistance of IBM Statistics Software Version 26.0. The findings of this study indicate that perceived ease of use significantly influences feature usage decisions, accounting for 54.6% of the variance. Furthermore, service quality has a significant impact, explaining 47.8% of the variance in feature usage decisions. Both the perceived ease of use and service quality significantly influence the decision to use features concurrently, with a combined coefficient value of 0.617 or 61.7%. It should be noted that 88.3% of the variance is attributed to factors not considered in this study